Multivalent vaccines demonstrate immunogenicity and protect against Coxiella burnetii aerosol challenge - Jan, Sharon; Fratzke, Alycia P.; Felgner, Jiin; Hernandez-Davies, Jenny E.; Liang, Li; Nakajima, Rie; Jasinskas, Algimantas; Supnet, Medalyn; Jain, Aarti; Felgner, Philip L.; Davies, D. Huw; Gregory, Anthony E. (Frontiers in Immunology, 2023)
Vaccines are among the most cost-effective public health measures for controlling infectious diseases.Coxiella burnetii is the etiological agent of Q fever, a disease with a wide clinical spectrum that ranges from mild symptoms, such as fever and fatigue, to more severe disease such as pneumonia and hepatitis. The formalin-inactivated whole cell vaccine Q-VAX® contains hundreds of antigens from the organisms and confers lifelong protection in humans, but prior sensitization from infection or vaccination can result in deleterious reactogenic responses to vaccination. Consequently, there is great interest in developing non-reactogenic alternatives based on adjuvanted recombinant proteins. In this study, we aimed to develop a multivalent vaccine that conferred protection with reduced reactogenicity.We hypothesized that a multivalent vaccine consisting of multiple antigens would be more immunogenic and protective than a monovalent vaccine owing to the large number of potential protective antigens in the C. burnetii proteome. To address this, we identify immunogenic T and B cell Multivalent vaccines demonstrate immunogenicity and protect against Coxiella burnetii aerosol challenge 2 antigens, and selected proteins were purified and evaluated with a novel combination adjuvant (IVAX-1), with or without C. burnetii LPS in immunogenicity studies in vivo in mice and in a Hartley guinea pig intratracheal aerosol challenge model using C. burnetii strain NMI RSA493. The data showed that multivalent vaccines are more immunogenic than monovalent vaccines, and more closely emulate the protection achieved by Q-VAX. Although 6 antigens were the most immunogenic, we also discovered that multiplexing beyond 4 antigens introduces detectable reactogenicity, indicating there is an upper limit to the number of antigens that can be safely included in a multivalent Q-fever vaccine. C. burnetii LPS also demonstrates efficacy as a vaccine antigen in conferring protection in an otherwise monovalent vaccine formulation, suggesting that its addition in multivalent vaccines, as demonstrated by a quadrivalent formulation, would improve protective responses.